203k views
2 votes
1) x+3 - 5x + 7 + 4y​

User Stitakis
by
5.8k points

2 Answers

4 votes

Answer:

x = 2.5 + y

Explanation:

Simplifying

x + 3 + -5x + 7 + 4y = 0

Reorder the terms:

3 + 7 + x + -5x + 4y = 0

Combine like terms: 3 + 7 = 10

10 + x + -5x + 4y = 0

Combine like terms: x + -5x = -4x

10 + -4x + 4y = 0

Solving

10 + -4x + 4y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10' to each side of the equation.

10 + -4x + -10 + 4y = 0 + -10

Reorder the terms:

10 + -10 + -4x + 4y = 0 + -10

Combine like terms: 10 + -10 = 0

0 + -4x + 4y = 0 + -10

-4x + 4y = 0 + -10

Combine like terms: 0 + -10 = -10

-4x + 4y = -10

Add '-4y' to each side of the equation.

-4x + 4y + -4y = -10 + -4y

Combine like terms: 4y + -4y = 0

-4x + 0 = -10 + -4y

-4x = -10 + -4y

Divide each side by '-4'.

x = 2.5 + y

User DaveX
by
5.7k points
5 votes
Answer:

~ -4x+4y+10

Explanation:

~ We have to collect like terms such as all the x’s, y and the normal numbers.

~ Then add like terms together: x-5x, 4y plus nothing, 3+7

~ After adding them, you should get -4x+4y+10.
User Jmt
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.